GATING OF HCN CHANNELS BY CYCLIC NUCLEOTIDES: RESIDUE CONTACTS THAT UNDERLIE LIGAND BINDING, SELECTIVITY AND EFFICACY - Zhou, Lei (2007)
Cyclic nucleotides regulate the activity of various proteins by interacting with a conserved cyclic nucleotide-binding domain (CNBD). Although X-ray crystallographic studies have revealed the structures of several CNBDs, the residues responsible for generating the high efficacy with which ligand binding leads to protein activation remain unknown. Here we combine molecular dynamics simulations with mutagenesis to identify ligand contacts important for the regulation of the hyperpolarization-activated HCN2 channel by cyclic nucleotides. Surprisingly, out of seven residues that make strong contacts with ligand, only R632 in the C-helix of the CNBD is essential for high ligand efficacy, due to its selective stabilization of cNMP binding to the open state of the channel. Principle component analysis suggests that a local movement of the C-helix upon ligand binding propagates through the CNBD of one subunit to the C-linker of a neighboring subunit to apply force to the gate of the channel.